International Joint Conference on Neural Networks 1989
DOI: 10.1109/ijcnn.1989.118316
|View full text |Cite
|
Sign up to set email alerts
|

Use of a neural net computer system for analysis of flow cytometric data of phytoplankton populations

Abstract: Flow cytometry has been used over the past 5 years to begin detailed exploration of the distribution and abundance of picoplankton in the oceans. Light scattering and fluorescence measurements on individual plankton cells in seawater samples allow construction of population signatures from size and pigment characteristics. The use of "list mode" data has made these studies possible, but on-shore analysis of copious data does not permit on-site reexamination of important or unexpected observations, and overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Whereas multivariate statistical approaches have been used (Demers et al 1992;Carr et al 1996), and can be very successful if the appropriate technique can be found, this is often not simple, and invalid assumptions about distributions can cause major problems. Artificial neural networks (ANNs) on the other hand, do not require a-priori knowledge of underlying distributions, once trained they can make identifications in near real-time and have been shown to have considerable potential for identifying phytoplankton from AFC data (e.g., Frankel et al, 1989Frankel et al, , 1996Boddy et al, 1994;Wilkins et al, 1994Wilkins et al, , 1996 and from morphometric data (e.g., Culverhouse et al, 1994Culverhouse et al, , 1996Williams et al, 1994). Species identification is not always possible based on light scatter and fluorescence characteristics, due either to similarities in the optical characteristics between species or to certain species having a wide range of optical characteristics, such as with clumped cells or chains.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas multivariate statistical approaches have been used (Demers et al 1992;Carr et al 1996), and can be very successful if the appropriate technique can be found, this is often not simple, and invalid assumptions about distributions can cause major problems. Artificial neural networks (ANNs) on the other hand, do not require a-priori knowledge of underlying distributions, once trained they can make identifications in near real-time and have been shown to have considerable potential for identifying phytoplankton from AFC data (e.g., Frankel et al, 1989Frankel et al, , 1996Boddy et al, 1994;Wilkins et al, 1994Wilkins et al, , 1996 and from morphometric data (e.g., Culverhouse et al, 1994Culverhouse et al, , 1996Williams et al, 1994). Species identification is not always possible based on light scatter and fluorescence characteristics, due either to similarities in the optical characteristics between species or to certain species having a wide range of optical characteristics, such as with clumped cells or chains.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to point out that the subjective nature of choosing n is not a weakness inherent in the curve-fitting method itself. The same considerations apply when one draws bitmaps by inspection or when one establishes training sets for neural networks that perform machine pattern recognition (Frankel et al 1989).…”
Section: Ef)mentioning
confidence: 99%
“…Recently, the problem of pattern recognition in phytoplankton sizefluorescence signatures has been addressed by neural network computation (Frankel et al 1989).…”
mentioning
confidence: 99%
“…In conclusion, until and unless mainstream manufacturers provide an integrated solution to the acquisition and COMMUNICATION TO THE EDITOR automated interpretation of flow cytometric, the application of techniques, such as, ANNs will remain rare, as they have been for the last 20 years (9). As such software is unlikely to become commercially available in the short term the flow cytometry community may benefit from investigating further the tools, such as, ratio calculation, that are provided in data acquisition software.…”
Section: Introductionmentioning
confidence: 99%